Early Use of N-acetylcysteine With Nitrate Therapy in Patients Undergoing Primary Percutaneous Coronary Intervention for ST-Segment–Elevation Myocardial Infarction Reduces Myocardial Infarct Size (the NACIAM Trial [N-acetylcysteine in Acute Myocardial Infarction]). Issue 10 (5th September 2017) - Pasupathy, Sivabaskari; Tavella, Rosanna; Grover, Suchi; Raman, Betty; Procter, Nathan E.K.; Du, Yang Timothy; Mahadavan, Gnanadevan; Stafford, Irene; Heresztyn, Tamila; Holmes, Andrew; Zeitz, Christopher; Arstall, Margaret; et al.
Abstract : Background: Contemporary ST-segment–elevation myocardial infarction management involves primary percutaneous coronary intervention, with ongoing studies focusing on infarct size reduction using ancillary therapies. N-acetylcysteine (NAC) is an antioxidant with reactive oxygen species scavenging properties that also potentiates the effects of nitroglycerin and thus represents a potentially beneficial ancillary therapy in primary percutaneous coronary intervention. The NACIAM trial (N-acetylcysteine in Acute Myocardial Infarction) examined the effects of NAC on infarct size in patients with ST-segment–elevation myocardial infarction undergoing percutaneous coronary intervention. Methods: This randomized, double-blind, placebo-controlled, multicenter study evaluated the effects of intravenous high-dose NAC (29 g over 2 days) with background low-dose nitroglycerin (7.2 mg over 2 days) on early cardiac magnetic resonance imaging–assessed infarct size. Secondary end points included cardiac magnetic resonance–determined myocardial salvage and creatine kinase kinetics. Results: Of 112 randomized patients with ST-segment–elevation myocardial infarction, 75 (37 in NAC group, 38 in placebo group) underwent early cardiac magnetic resonance imaging. Median duration of ischemia pretreatment was 2.4 hours. With background nitroglycerin infusion administered to all patients, those randomized to NAC exhibited an absolute 5.5% reduction in cardiac magnetic resonance–assessed infarct size relative to placebo (median, 11.0%; [interquartile range 4.1, 16.3] versus 16.5%; [interquartile range 10.7, 24.2]; P =0.02). Myocardial salvage was approximately doubled in the NAC group (60%; interquartile range, 37–79) compared with placebo (27%; interquartile range, 14–42; P <0.01) and median creatine kinase areas under the curve were 22 000 and 38 000 IU·h in the NAC and placebo groups, respectively ( P =0.08). Conclusions: High-dose intravenous NAC administered with low-dose intravenous nitroglycerin is associated with reduced infarct size in patients with ST-segment–elevation myocardial infarction undergoing percutaneous coronary intervention. A larger study is required to assess the impact of this therapy on clinical cardiac outcomes. Clinical Trial Registration: Australian New Zealand Clinical Trials Registry. URL:http://www.anzctr.org.au/ . Unique identifier: 12610000280000. Abstract : Supplemental Digital Content is available in the text.